Genetic Analysis of Components of Resistance to Philippine Downy Mildew In Maize - D. Ruswandi; A. L. Carpena; R. M. Lantican; A. M. Salazar; D. M. Hautea; A. D. Raymundo (Zuriat, 2002)
The genetics of resistance to Philippine downy mildew in maize (Zea mays L.) caused by Peronosclerospora philippinensis was studied in progeny derived from crosses between the resistant inbred P 345 and susceptible inbred Pi 17 and Pi 23. Plant generations used in this study were the PS (susceptible lines Pi 17 and Pi 23); PR (P 345); extensively F1, F2; F3; BS and BR. Plants at three leaf stages were artificially inoculated and evaluated for components of resistance, namely: disease incidence, disease severity, onset of systemic symptom, area under disease progress curve, and rate of downy mildew development. Analysis of generation means indicate that additive- dominance with epistasis gene effect play important role in all components of resistance to Philippines downy mildew.